THE IMPACT OF CO2 LASER TREATMENT ON GRAPHENE-MODIFIED KM2-440 BALLISTIC KEVLAR FABRIC AND ITS PROPERTY CHANGES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study investigates the laser marking of graphene-modified KM2-440 ballistic Kevlar fabric, exploring how different laser parameters affect its properties. A 1x4 matrix was marked on the fabric using the SUNTOP ST-CC9060 laser system, with each square measuring 30 mm in length and 40 mm in width. Our adjustments to the laser marking parameters encompassed variations in speed and power. Specifically, the speed ranged from 100 mm/s to 150 mm/s, while the power varied between 8.5% and 8.8%. A constant step size (Δx) of 0.08 mm was maintained for all markings. These parameter variations were studied to assess their impact on the fabric’s mechanical properties, surface roughness, and durability. Advanced testing methods, including the Olympus LEXT OLS5000 3D Measuring Laser Microscope, were employed to examine the correlation between laser marking parameters and the changes in the fabric's ballistic performance. The findings provide significant insights into the effects of laser processing on the structural integrity and performance of graphene-modified Kevlar fabrics. This research not only contributes to optimizing laser marking parameters for enhanced fabric durability but also offers valuable knowledge on how graphene incorporation affects the ballistic characteristics of Kevlar in the context of laser treatment.